Whistle-Blowing and Morality - Bouville, Mathieu (Journal of business ethics, 2008)
Whistle-blowing is generally considered from the viewpoint of professional morality. Morality rejects the idea of choice and the interests of the professional as immoral. Yet the dreadful retaliations against the messengers of the truth make it necessary for morality to leave a way out of whistle-blowing. This is why it forges rights (sometimes called duties) to trump the duty to the public prescribed by professional codes. This serves to hide the obvious fact that whether to blow the whistle is indeed a choice, not a matter of objective duty. One should also notice that if it fails to achieve anything then blowing the whistle was the wrong decision (or maybe the right decision that nobody would want to make). There is nevertheless a tendency to judge it based on the motivation of the whistle blower. In a way, whistle blowers should strive to act like saints. Yet, it is logically impossible to hold both whistle-blowing as mandatory and whistle-blowers as heroes or saints. Moreover, this tends to value the great deeds of a few over the lives of the many, which is incompatible with the basic assumptions of morality. But consistency is not a main feature of professional morality.